Commensal Bacteria in the Cystic Fibrosis Airway Microbiome Reduce P. aeruginosa Induced Inflammation - Tony-Odigie, Andrew; Wilke, Leonie; Boutin, Sébastien; Dalpke, Alexander H.; Yi, Buqing (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic Pseudomonas aeruginosa infections play an important role in the progress of lung disease in patients suffering from cystic fibrosis (CF). Recent studies indicate that polymicrobial microbiome profiles in the airway are associated with less inflammation. Thus, the hypothesis was raised that certain commensal bacteria might protect the host from inflammation. We therefore performed a screening study with commensals isolated from CF airway microbiome samples to identify potential beneficial commensals. We isolated more than 80 aerobic or facultative anaerobic commensal strains, including strains from genera Streptococcus, Neisseria, Actinomyces, Corynebacterium, Dermabacter, Micrococcus and Rothia. Through a screening experiment of co-infection in human epithelial cell lines, we identified multiple commensal strains, especially strains belonging to Streptococcus mitis, that reduced P. aeruginosa triggered inflammatory responses. The results were confirmed by co-infection experiments in ex-vivo precision cut lung slices (PCLS) from mice. The underlying mechanisms of the complex host-pathogen-commensal crosstalk were investigated from both the host and the bacterial sides with a focus on S. mitis. Transcriptome changes in the host in response to co-infection and mono-infection were evaluated, and the results indicated that several signalling pathways mediating inflammatory responses were downregulated by co-infection with S. mitis and P. aeruginosa compared to P. aeruginosa mono-infection, such as neutrophil extracellular trap formation. The genomic differences among S. mitis strains with and without protective effects were investigated by whole genome sequencing, revealing genes only present in the S. mitis strains showing protective effects. In summary, through both in vitro and ex vivo studies, we could identify a variety of commensal strains that may reduce host inflammatory responses induced by P. aeruginosa infection. These findings support the hypothesis that CF airway commensals may protect the host from inflammation.